2008
DOI: 10.1016/j.jcrs.2007.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological and immunofluorescence evaluation of bimanual and coaxial phacoemulsification incisions in rabbits

Abstract: Corneal incisions for bimanual phacoemulsification were more prone to damage than those for coaxial phacoemulsification. This may be attributed to the absence of a sleeve, which places the incision tunnel in direct contact with the metal phaco tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Importantly, to our knowledge, there is only 1 clinical study that casts light on the incision integrity of CCIs used for bimanual phacoemulsification versus coaxial phacoemulsification. 17 This study found greater ingress of trypan blue into the anterior chamber in the bimanual eyes versus the microcoaxial and the coaxial eyes. The authors suggested that, while it is tempting to perform surgery through incisions as small as possible, surgeons should minimize incision distortion as it could jeopardize incision integrity.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Importantly, to our knowledge, there is only 1 clinical study that casts light on the incision integrity of CCIs used for bimanual phacoemulsification versus coaxial phacoemulsification. 17 This study found greater ingress of trypan blue into the anterior chamber in the bimanual eyes versus the microcoaxial and the coaxial eyes. The authors suggested that, while it is tempting to perform surgery through incisions as small as possible, surgeons should minimize incision distortion as it could jeopardize incision integrity.…”
Section: Discussionmentioning
confidence: 55%
“…16,17 In rabbit eyes, after bimanual surgery, there was more irregularity to the incision margins, more stromal swelling, and more disruption of stromal collagen fibers than after coaxial surgery. Importantly, to our knowledge, there is only 1 clinical study that casts light on the incision integrity of CCIs used for bimanual phacoemulsification versus coaxial phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The findings recorded were at the roof and floor of the incision tunnel. Characteristics of the incision were evaluated by observing alterations in the arrangement and appearance of the epithelium, stromal fibers, keratocyte nuclei, tunnel margin, Descemet membrane, and endothelium.…”
Section: Materials and Methods Experimental Trialmentioning
confidence: 99%
“…3 Localization of collagen type I was performed using a primary anticollagen type I antibody that does not bind to denatured collagen type I and Alexa Fluor 488 (fluorescent dye obtained from Molecular Probes, Invitrogen) tagged secondary antibody (green). The nuclei were stained with 4',6-diamidino-2-phenylindole (DAPI, Sigma Aldrich) (blue).…”
Section: Materials and Methods Experimental Trialmentioning
confidence: 99%